No easy way out: towards a framework concept of long-term governance - Dirk Scheer; Sandra Venghaus; Stefania Sardo; Sascha Stark; Sophie Kuppler; Michael W. Schmidt; Carsten Hoyer-Klick (Energy, Sustainability and Society)
Abstract Background Problems such as climate change, environmental pollution, nuclear disposal and unsustainable production and consumption share a common feature: they pose long-term challenges because of their complex nature, potentially severe consequences, and the demanding problem-solving paths. These challenges may have long-lasting impacts on both present and future generations and, therefore, require to be addressed through a long-term governance perspective, i.e., coherent and consistent policy-making across sectors, institutions, and temporal scales. Dealing with these challenges is a core task of policy-making in modern societies, which requires problem-solving skills and capabilities. In this context, we identify long-term governance traces in the literature, illustrate the case of energy transition towards renewable energy systems as a long-term governance case, and elaborate on the scope and definition of long-term governance and its research. Main text We elaborate an analytical framework for long-term governance (LTG), based on five building blocks: the ‘environment’, which details the policy-making arena; the ‘policy issues’, which elaborates on the problems to be dealt with by LTG; the ‘key challenges and driving force’, revealing LTG mechanisms; the ‘key strategies’, in which promising approaches for LTG are identified; and the ‘policy cycle’, where governance impacts on different policy phases are discussed. In essence, we understand long-term governance at its core as a reflexive policy-making process to address significant enduring and persistent problems within a strategy-based decision-making arena to best prepare for, navigate through, and experiment with a changing environment. Conclusions The framework does not describe specific processes or individual cases in detail. Instead, it should be understood as an illustration of long-term governance characteristics at a more general level. Such a framework may help to structure the field of long-term policy-making, guide future research on conceptual, comparative, and empirical in-depth studies, and may provide orientation and action knowledge for making our governance system sustainable. Stimulating and broadening research on long-term issues seems indispensable, given the existence of several ‘grand challenges’ that require successful long-term governance.